Potential Of Pineapple Peel Waste With Tapioca Starch In Making Edible Film - Zahara Nuril Firdausi; Syaifudin Moch; Medya Ayunda Fitri; Azizah Zahrotul (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2026)
Most pineapple peels are discarded as waste, although they contain 8.3% pectin, a valuable component for edible film production. This study aimed to examine the effects of temperature and extraction time on pectin yield and to evaluate the texture of edible films produced with glycerol. The overall process consisted of three stages: pineapple peel pretreatment, pectin extraction, and edible film preparation. Results showed that extending extraction time increased the amount of pectin obtained. The maximum yield was recorded at 125 minutes and 100°C, reaching 8.985 grams. In terms of tensile strength, higher extraction temperatures accelerated gelatinization and improved film strength. The best tensile strength was obtained at 70°C for 150 minutes, achieving 34.898 N/mm. Organoleptic evaluation involved 208 responses, where 49.5% rated the film as normal (103 responses), 37.5% as like (78 responses), 4.8% as really like (10 responses), and 8.2% as don’t like (17 responses). Overall, edible films made from pineapple peel and tapioca were considered acceptable. The highest preference was observed for texture, followed by color, while taste and flavor scored lower. These findings highlight the potential of pineapple peel films, although further formulation improvements are needed for better consumer acceptance.